ELLE Glam Fitness Complete Cardio : [The Dance-Inspired Workout to a Leaner Body] - St. Michael, Melyssa (New York Filipacchi, 2008)
Presents a dance workout with step-by-step instructions designed to reduce weight, increase cardiovascular health, and shape the body, and includes a fourteen-day meal plan and a thirty-minute workout DVD.
Keywords: Cardiovascular fitness -- Reducing exercises -- Physical fitness